Humanitarianism : keywords - De Lauri, Antonio (Online access: Brill Brill Open e-Books., 2020)
"Humanitarianism: Keywords is a comprehensive dictionary designed as a compass for navigating the conceptual universe of humanitarianism. It is an intuitive toolkit to map contemporary humanitarianism and to explore its current and future articulations. The dictionary serves a broad readership of practitioners, students, and researchers by providing informed access to the extensive humanitarian vocabulary"--